(untitled) (MSW Management Journal, 2026)
Personalization enhances customer perception by increasing perceived relevance, reducing information overload, and strengthening emotional engagement. From a cognitive processing perspective, personalized stimuli are more likely to activate reward centers in the brain, foster positive affect, and improve recall. Finally, it concludes that Neuromarketing goes beyond demographics to identify "hidden" preferences by mapping how individuals process information and make decisions, such as which visual elements in an ad capture attention